Regulatory T cells facilitate the nuclear accumulation of inducible cAMP early repressor (ICER) and suppress nuclear factor of activated T cell c1 (NFATc1) - Vaeth, Martin (National Academy of Sciences, 2011)
Inducible cAMP early repressor (ICER) is a transcriptional repressor, which, because of alternate promoter use, is generated from the 3′ region of the cAMP response modulator (Crem) gene. Its expression and nuclear occurrence are elevated by high cAMP levels in naturally occurring regulatory T cells (nTregs). Using two mouse models, we demonstrate that nTregs control the cellular localization of ICER/CREM, and thereby inhibit IL-2 synthesis in conventional CD4(+) T cells. Ablation of nTregs in depletion of regulatory T-cell (DEREG) mice resulted in cytosolic localization of ICER/CREM and increased IL-2 synthesis upon stimulation. Direct contacts between nTregs and conventional CD4(+) T cells led to nuclear accumulation of ICER/CREM and suppression of IL-2 synthesis on administration of CD28 superagonistic (CD28SA) Ab. In a similar way, nTregs communicated with B cells and induced the cAMP-driven nuclear localization of ICER/CREM. High levels of ICER suppressed the induction of nuclear factor of activated T cell c1 (Nfatc1) gene in T cells whose inducible Nfatc1 P1 promoter bears two highly conserved cAMP-responsive elements to which ICER/CREM can bind. These findings suggest that nTregs suppress T-cell responses by the cAMP-dependent nuclear accumulation of ICER/CREM and inhibition of NFATc1 and IL-2 induction.